Power and Agency in Newfoundland and Labrador's History - Cadigan, Sean (Labour / Le Travail, 2004)
Reviewed: Between History and Tomorrow: Making and Breaking Everyday Life in Rural Newfoundland. Sider, Gerald M.

The Moral Economy of the Commons: Ecology and Equity in the Newfoundland Cod Fishery, 1815-1855 - Cadigan, Sean (Labour / Le Travail, 1999)
A sense of determinism about the emergence of capitalism and the ruthless over-exploitation of nature in European colonial expansion pervades much of North American environmental and ecological history. The attempts of 19th-century Newfoundland fishing people to regulate access to common-property marine resources suggests that some European settlers were also capable of non-capitalist forms of ecological management. Fishers protested against the introduction of new fishing technology in response to localized exhaustion of cod stocks. Some of these protests involved the destruction of newer equipment, while others were anonymous assaults on the equipment's owners. The protests represented attempts to forestall the depletion of marine resources by the further capitalization of the fishery. By the late 1840s the demands for conservation measures became more organized politically under the leadership of mercantile agent Willam Kelson. Although he was conservative and paternalistic, Kelson's criticism of the unrestrained employment of technology in the fishing industry had radical implications. Kelson supported the desire to preserve a customary and equitable right of access to fish for present and future generations. The preservation of equitable access may been seen as an ecological norm of a moral economy that ran counter to the individualistic and accumulative values of a nascent local capitalist political economy.

Battle Harbour in Transition: Merchants, Fishennen, and the State in the Struggle for Relief in a Labrador Community during the 1930s - Cadigan, Sean (Labour / Le Travail, 1990)
The early 1930s witnessed the deterioration of truck relationships between fishermen and merchants in Battle Harbour, a Newfoundland fishing community located on the coast of Labrador. By taking advantage of changes in the fishery, more prosperous fishermen began to deal with other firms, undercutting Baine, Johnston's domination of Battle Harbour. As Baine, Johnston withdrew winter credit, poorer fishermen threatened the firm with direct, violent action which neither the merchant nor the state were able to deal with except by granting relief. Such actions by Battle Harbour fishermen indicate that they were able to step outside the supposed limits of the culture of their kin-based villages, and confront directly the exploitation of merchant capital in the cod fishery.
Keywords: COD fisheries; FISHERS; HARBORS; INDUSTRIAL management; Industrial relations; Labor Unions; Labor disputes; MERCHANTS; Social conditions; Working class

Seafaring Labour: The Merchant Marine of Atlantic Canada, 1820-1914 - Cadigan, Sean (Labour / Le Travail, 1990)
The article reviews the book "Seafaring Labour: The Merchant Marine of Atlantic Canada, 1820-1914," by Eric W. Sager.
Keywords: Merchant marine; Nonfiction; REVIEWS; SAGER; Eric W.; SEAFARING Labour: The Merchant Marine of Atlantic Canada 1820-1914 (Book); books

An Introduction - Cadigan, Sean (Labour / Le Travail, 2015)
Introduces papers given at a Brock University panel on the television show, "Bomb Girls." The series, which was described as a "'World War II drama-cum-soap opera focusing on the Canadian homefront and the gals (and guys) working at a munitions factory,'" aired on the Global Television Network during the 2012-13 seasons.

Merchant Capital, the State, and Labour in a British Colony: Servant-Master Relations and Capital Accumulation in Newfoundland’s Northeast-Coast Fishery, 1775-1799 - Cadigan, Sean (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
This paper uses a case study of class struggle in the late-eighteenth-century Newfoundland fishery to examine the relationship between merchant capital and the employment of wage labour in staple production in early colonial development. Using a modified version of the staple model which emphasises the role of the class relations and institutional structures of staple industries on long-term development, it finds that British regulation of wages to protect the migratory fishery stymied the extensive employment of wage labour by resident planters. Evidence drawn from court records suggests that fishing servants used the law to prevent erosion of wages due from planters at the end of a fishing season by ignoring mandatory preseason contracts or account overcharges. Servants enjoyed less, but still formidable, success in winning suits brought about by masters for neglect. By using wage law beyond the intentions of its British makers, servants forced planters increasingly to rely on family labour rather than wage labour. The struggles of wage labourers with their employers, rather than merchant conservatism as such, contributed to Newfoundland's long-term domination by merchant truck with fishing families.

Ships of State: Literature and the Seaman’s Labour in Proto-Imperial Britain - Cadigan, Sean T. (Labour / Le Travail, 2026)
This article reviews the book, "Ships of State: Literature and the Seaman’s Labour in Proto-Imperial Britain," by Laurie Ellinghausen.

The Fishermen's Frontier: People and Salmon in Southeast Alaska - Cadigan, Sean T. (Labour / Le Travail, 2010)
The article reviews the book, "The Fishermen's Frontier: People and Salmon in Southeast Alaska," by David F. Arnold.
Keywords: ALASKA; ARNOLD; David F.; BOOKS – Reviews; FISHERMEN'S Frontier: People & Salmon in Southeast Alaska; The (Book); Fisheries; History; Nonfiction

Paternalism and Politics: Sir Francis Bond Head, the Orange Order, and the Election of 1836 - Cadigan, Sean T. (Canadian Historical Review, 1991)

Boom, Bust and Bluster: Newfoundland and Labrador's "Oil Boom" and Its Impacts on Labour - Cadigan, Sean T. (Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada, 2012)
Analyzes the effects of the off-shore oil boom of the late 1990s in Newfoundland and Labrador, that has exacerbated the urban-rural divide. Concludes that despite the rhetoric of transformation, the provincial economy has not basically changed.
Keywords: Business and politics; Economic conditions; Employee rights; Industrial relations; Labor policy

Obituary: Irene Whitfield - Kealey, Gregory S.; Cadigan, Sean (Labour / Le Travail, 2013)
Pays homage to Irene Whitfield (1941-2013), who was managing editor of the journal from 1982 to 2007.
Keywords: PERIODICAL editors; WHITFIELD; Irene

A Welcome to Canadian Association for Work and Labour Studies (CAWLS) Members = Bienvenue aux membres de l’Association canadienne d’études du travail et du syndicalisme (Acets) - Kealey, Gregory S.; Cadigan, Sean (Labour / Le Travail, 2015)
Announces that the journal is now a joint partnership of the Canadian Committee on Labour History with Athabaska University Press, in affiliation with the Canadian Association of Labour Studies.
Issue 76, Fall 2015

Editor’s Note: A Welcome to Canadian Association for Work and Labour Studies (CAWLS) Members = Bienvenue aux membres de l’Association canadienne d’études du travail et du syndicalisme (Acets) - Cadigan, Sean; Kealey, Gregory S. (Labour / Le Travail, 2015)
CAWLS is joining the Canadian Committee on Labour History family. The journal is now co-published by CCLH and Athabasca University Press, in affiliation with CAWLS.

E.P. Thompson's The Making of the English Working Class at Fifty - Palmer, Bryan D.; Merrill, Michael; Way, Peter; Loo, Tina; Levine, David; Hill, Rebecca; Cadigan, Sean; Jacob, Margaret C. (Labour / Le Travail, 2013)
The article introduces the first of a two-part series in the journal on the 50th anniversary of the publication of "The Making of the English Working Class" by British historian E.P. Thompson. In addition to describing their own responses, the authors discuss how the book has influenced working-class studies, its political impact, Thompson's Marxism, and his critique of Methodism. The articles in the presentation include: "E.P. Thompson’s Capital: Political Economy in The Making" by Michael Merrill; "Among the Autodidacts: The Making of E.P. Thompson" by Margaret C. Jacob; “The something that has called itself ‘Marxism’” by Peter Way; "The Face of Power" by Tina Loo; "A Definitive ‘And fookin’ Amen to that!" by David Levine; "Frame Breaking Then and Now" by Rebecca Hill; and "The Privilege of History" by Sean Cadigan.
Keywords: 20th century; LABOR movement – History; MAKING of the English Working Class; The (Book); MARXIST philosophy; METHODISM; SOCIAL history – 20th century; THOMPSON; E. P. (Edward Palmer); 1924-1993; WORKING class – Research